Cloning of D-glucose dehydrogenase with a narrow substrate specificity from Bacillus thuringiensis M15 - Boontim N. (2014)
We have cloned an ORF of Bacillus thuringiensis M15, which encodes a protein sharing high similarity with D-glucose dehydrogenase. A high-expression plasmid (pBtGDH) for the ORF was constructed. Escherichia coli JM 109 transformed with pBtGDH exhibited D-glucose dehydrogenase activity, and the enzyme was purified by 3 chromatographic steps to homogeneity with 6.9 fold and a final yield of 13%. The purified enzyme has highly narrow substrate specificity for glucose and 2-deoxy-D-glucose and showed no activity with any other sugars we tested. The properties of the purified enzyme were similar to those of the D-glucose dehydrogenase (BtGDH) that is mainly produced in B. thuringiensis M15. These results show that the cloned gene encodes BtGDH, as we previously reported. This is the first report to determine the sequence of the enzyme with narrow substrate specificity. BtGDH shows 89% sequence similarity with D-glucose dehydrogenase from Bacillus megaterium IWG3 (GDH-IWG3), which has broad substrate specificity. A comparative analysis between BtGDH and GDH-IWG3 will reveal the differences between them and show the narrow specific activity of BtGDH.